Navigating uncharted waters: black swan events and global supply chain resilience - Gábor, Nagy; Szentesi, Szabolcs (Advanced Logistic Systems - Theory and Practice, 2024)
This paper delves into the critical realm of global supply chain management, exploring the challenges posed by black swan events—unpredictable and high-impact occurrences. In navigating these uncharted waters, the focus is on bolstering resilience to ensure the continuity and adaptability of supply chains. The study emphasizes proactive risk assessment and scenario planning, advocating for diversification, redundancy, and the integration of technology. Collaboration, agile supply chain practices, and resilient financial planning are deemed pivotal, along with a commitment to regulatory compliance and employee well-being. The pursuit of continuous improvement and the optimization of global networks round out a comprehensive strategy to fortify supply chains against the unforeseen disruptions that characterize the contemporary business landscape.